The Effect of Resistance Band Exercise Variations on Dollyo Chagi Kick Results Taekwondo Club Global Taekwondo Academy - I Bagus Endrawan; Martinus Martinus; Ahmad Yani; Adi S; Hilmy Aliriad (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2023)
This study aims to determine the effect of resistance band variations on the results of Global Taekwondo Academy taekwondo dollyo chagi kicks. This type of research is experimental, with data collection techniques using documentation and tests. Taekwondo kick speed test using Measurement Foundation Skill Taekwondo The test is carried out by kicking as fast as possible within 10 seconds. The research subjects were five athletes from the Global Taekwondo Academy. Data analysis technique using the t-test From the results of data analysis, it was obtained that the average value of Resistance Band exercises was tcount = 8.850 > ttable = 1.729 and at a significant level of 5%. These results can be interpreted as indicating that there is an effect of resistance band variations on the results of the Global Taekwondo Academy dollyo chagi kick. The conclusion of this study is that there is an influence of resistance band variations on the results of dollyo chagi taekwondo kicks at Global Taekwondo Academy.